Transcranial Direct Current Stimulation on Parietal Operculum Contralateral to the Moving Limb Does Not Affect the Programming of Intra-Limb Anticipatory Postural Adjustments - Marchese, Silvia M.; Esposti, Roberto; Bolzoni, Francesco; Cavallari, Paolo (Frontiers in Physiology, 2019)
Recent data suggest that the parietal operculum acts as an integration centre within a multimodal network, originating from different primary sensory and motor cortices and projecting to frontal, parietal and temporal cortical hubs, which in turn govern cognitive and motor functions. Thus, parietal operculum might also play a crucial role in the integrated control of voluntary movement and posture. As a first step to test this hypothesis, the Anticipatory Postural Adjustments (APAs) stabilizing the arm when the index-finger is briskly flexed were recorded, on the preferred side, in three groups of 10 healthy subjects, before, during and after CATHODAL or ANODAL transcranial Direct Current Stimulation (tDCS, 20 min at 2 mA) applied over the contralateral Parietal Operculum (coPO). Results were compared to those obtained in a SHAM group. In agreement with literature, in the SHAM group the activation of the prime mover Flexor Digitorum Superficialis was preceded by an inhibitory APA in Biceps Brachii and Anterior Deltoid, and almost simultaneous to an excitatory APA in Triceps Brachii. The same pattern was observed in both the CATHODAL and ANODAL groups, with no significant tDCS effects on APAs amplitude and timing. Index-finger kinematics were also unchanged. These negative results suggest that the coPO does not disturb the key network governing APAs in index-finger flexion. Since it has been well documented that such APAs share many features with those observed in trunk and limb muscles when performing several other movements, we suggest that coPO may not be crucial to the general APA control.